Immunoglobulin A Protease Variants Facilitate Intracellular Survival in Epithelial Cells By Nontypeable Haemophilus influenzae That Persist in the Human Respiratory Tract in Chronic Obstructive Pulmonary Disease - Murphy, Timothy F (J Infect Dis, 2017)
BACKGROUND: Nontypeable Haemophilus influenzae (NTHi) persists in the airways in chronic obstructive pulmonary disease (COPD). NTHi expresses 4 immunoglobulin (Ig)A protease variants (A1, A2, B1, B2) with distinct cleavage specificities for human IgA1. Little is known about the different roles of IgA protease variants in NTHi infection. METHODS: Twenty-six NTHi isolates from a 20-year longitudinal study of COPD were analyzed for IgA protease expression, survival in human respiratory epithelial cells, and cleavage of lysosomal-associated membrane protein 1 (LAMP1). RESULTS: IgA protease B1 and B2-expressing strains showed greater intracellular survival in host epithelial cells than strains expressing no IgA protease (P < .001) or IgA protease A1 or A2 (P < .001). Strains that lost IgA protease expression showed reduced survival in host cells compared with the same strain that expressed IgA protease B1 (P = .006) or B2 (P = .015). IgA proteases B1 and B2 cleave LAMP1. Passage of strains through host cells selected for expression of IgA proteases B1 and B2 but not A1. CONCLUSIONS: IgA proteases B1 and B2 cleave LAMP1 and mediate intracellular survival in respiratory epithelial cells. Intracellular persistence of NTHi selects for expression of IgA proteases B1 and B2. The variants of NTHi IgA proteases play distinct roles in pathogenesis of infection.